Drug rehabilitation treatment: The consistency practice of remembrance to Allah (Zikir) among drug addicts in Malaysia - Adam, Fadzli; Wan Ahmad, Wan Ibrahim; Anuar, Marhana Mohammed; Ab. Rahman, Asyraf (MCSER Publishing, Rome-Italy, 2015)
Various forms of treatment and rehabilitation, either traditional or spiritual, introduced to solve the problem of drug addiction among the youths in Malaysia.Remembrance to Allah (zikir) has been identified to give a positive effect in the drug rehabilitation process.This study aims to analyze the consistency levels of remembrance to Allah either aloud (jahar) and silent (khafi) remembrance between former drug addicts and relapse in the process of drug rehabilitation treatment in Malaysia.The data of the study is collected through quantitative and qualitative methods.A total of 60 people, 30 people are former addicts in Terengganu and 30 people are relapsed drug addicts under rehabilitation at Pondok Remaja Inabah rehabilitation centre (PRI) in Kedah and Terengganu, Malaysia are chosen as the respondent for survey procedure.In addition, there are also 10 key informants selected from these respondents for in depth interview procedure.Survey and structured interview data are analyzed using triangulation methods.The results show significant difference between the two groups in relation to consistency practice of remembrance to Allah. Former drug addicts show more consistency in the practice of remembrance comparing to relapsed drug addicts.Therefore, the level of consistency is seen as an important contributing factor to prevent individuals from drug addiction.